The Verse Römerbrief 1, 19ff. On the Understanding of Abelard - Alexander Fidora (Patristica et Mediævalia, 2000)
Although over the last years scholarly work on Peter Abelard as both theologian and philosopher has increased rapidly, only little attention has been paid to his interpretation of St. Paul’s Epistle to the Romans. As it is known, this Epistle has played a major role throughout the entire Christian tradition in the determination of the relation between theology and philosophy, faith and reason. And so it has for Peter Abelard who most vigorously applied reason to the domain of faith. The following article tries to fill this gap in present research –or at least to give an impulse to fill it– by sketching the general outlines of Abelard’s interpretation across his works and comparing them to those of some of his contemporaries. It will show that Peter Abelard, at a certain point of his intellectual career, offers a very original, albeit exaggerated reading of Rom. 1, 19ff. which cannot be found in other scholars of his time nor in his most influential successor, Robert of Melun.